2013
DOI: 10.1128/iai.00914-12
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Inhibits Hyphal Morphogenesis and Virulence of Candida albicans

Abstract: The Gram-positive bacterium Enterococcus faecalis and the fungus Candida albicans are both found as commensals in many of the same niches of the human body, such as the oral cavity and gastrointestinal (GI) tract. However, both are opportunistic pathogens and have frequently been found to be coconstituents of polymicrobial infections. Despite these features in common, there has been little investigation into whether these microbes affect one another in a biologically significant manner. Using a Caenorhabditis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
134
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 65 publications
(80 reference statements)
12
134
1
1
Order By: Relevance
“…The protein responsible was identified as the bacteriocin EntV; this secreted protein demonstrated antihyphal and antivirulence properties without antagonising fungal growth [107•]. Co-infection of these organisms has been shown to attenuate C. albicans virulence in vivo, particularly with an initial administration of E. faecalis [108,109]. Interestingly, this effect was also mimicked in a murine oral candidiasis model, whereby initial administration of heatkilled bacteria was shown to have a protective antifungal effect [110].…”
Section: Endodontic Infections: Sinister Encounters In the Darkmentioning
confidence: 93%
See 1 more Smart Citation
“…The protein responsible was identified as the bacteriocin EntV; this secreted protein demonstrated antihyphal and antivirulence properties without antagonising fungal growth [107•]. Co-infection of these organisms has been shown to attenuate C. albicans virulence in vivo, particularly with an initial administration of E. faecalis [108,109]. Interestingly, this effect was also mimicked in a murine oral candidiasis model, whereby initial administration of heatkilled bacteria was shown to have a protective antifungal effect [110].…”
Section: Endodontic Infections: Sinister Encounters In the Darkmentioning
confidence: 93%
“…Based on existing knowledge of polymicrobial biofilm communities, these findings could complicate treatment regimens and provide a possible explanation for recurrent root canal infections. Mechanistically, E. faecalis integrates into Candida biofilms and reduces the overall biomass [105], and also been shown to negatively affect C. albicans hyphal formation [106]. The protein responsible was identified as the bacteriocin EntV; this secreted protein demonstrated antihyphal and antivirulence properties without antagonising fungal growth [107•].…”
Section: Endodontic Infections: Sinister Encounters In the Darkmentioning
confidence: 99%
“…The major signalling molecules produced by Gram-positive cocci are peptides, including CSPs and bacteriocins. There is evidence that peptides produced by S. mutans (Jarosz et al, 2009) and Enterococcus faecalis (Cruz et al, 2013) are inhibitory to filamentation by C. albicans. The ComCDE systems in S. gordonii, S. pneumoniae and S. mutans function as QS autoregulatory control systems, modulating gene expression patterns in different ways for the three streptococcal species (Vickerman et al, 2007;Mashburn-Warren et al, 2010;Son et al, 2012;Merritt & Qi, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Fusobacterium nucleatum, however, hyphal inhibition was contact dependent [13]. Interestingly, both probiotic and facultative pathogenic bacteria were shown to negatively affect hyphal formation [9,10,[12][13][14][15]. It, therefore, appears possible that the interaction with bacteria, rather than distinct environmental conditions or transcriptional programs, is responsible for the predominance of C. albicans yeast morphology in the gastrointestinal tract.…”
mentioning
confidence: 99%
“…In most studies, bacteria were found to inhibit fungal filamentation, often by secreted compounds that are linked to bacterial quorum sensing, virulence factors, or metabolism [9][10][11][12]. In the case of Fusobacterium nucleatum, however, hyphal inhibition was contact dependent [13].…”
mentioning
confidence: 99%